The Muslim diaspora in Britain and its literature - Hasan, Md. Mahmudul (2022)
Britain has reportedly had connection with Islam since the twelfth century, while the recorded history of the religion in the country dates back to the fourteenth century. References to Muslim places like Grenada and Turkey and to Muslim personalities like Al-Razi, Ibn Sina and Ibn Rushd are present in Geoffrey Chaucer’s The Canterbury Tales (1392). Queen Elizabeth I arguably sought military assistance from the Ottoman Empire against the Spanish Armada. All these suggest that the connection between Britain and Islam and Muslims is very old. Moreover, over centuries there have been many waves of immigration of Muslims into Britain from various parts of the world, especially from its former colonies. These and many other factors have contributed to an increasingly large Muslim community in today’s Britain. Among the Muslim population in the country, there are innumerable writers who have brought vibrancy, new life and a dynamic character to its literary scene. Given this background, this presentation aims to provide a bird’s eye view of the literary practices of the Muslim diaspora in Britain.